Generalization of Fuzzy Boundary in Fuzzy Bitopological Spaces - T. Thangam; K. Bageerathi (International Journal of Mathematics And its Applications, 2018)
Focus of this paper is to introduce the concept of fuzzy (τ_i, τ_j)-boundary and fuzzy C-(τ_i, τ_j)-boundary in fuzzy bitopological space where C: [0,1] → [0,1] is a complement function. Several examples are given to illustrate the concepts introduced in this paper.